Study to assess neuropathy severity in patients with diabetic foot problems - Narayana, Someshwara Rao Pallela (International Surgery Journal, 2020)
Background: Diabetic neuropathy is the most common complication of diabetes affecting 50% of the patients with type 1 and type 2 diabetes. Its late sequelae which include foot ulceration, charcot neuroarthropathy and occasionally amputation, should in many cases be preventable. Biothesiometry is a device which can measure the vibration perception threshold and guide the treatment as well as prevent further foot problems in such patients. Methods: In this study we included 65 patients with diabetic foot symptoms by random sampling technique between the age group of 40-75 years. All these patients were subjected to biothesiometer testing. The response was measured as vibration perception threshold (VPT). The variation of VPT in different conditions was established. Results: Among 65 patients, 40(61%) patients had painful sensation, VPT ranging from 16 V to 25 V, 6 (0.09%) patients had callus, dry foot or pigmentation with VPT 25-35 V, 12 (18.4%) patients had callus ulcer with VPT 36-45 V, 3 (0.046%) patients had both ulcer and skin changes with VPT 45-50 V and 4 (0.06%) patients presented with deformity and VPT 50 V. Conclusions: The study concluded that risk of ulceration is high with increased VPT. Hence, early detection of raised VPT would help the clinicians not only to guide the patients about the high risk of ulceration but it as well will help in educating the patient and emphasizing the need for proper glycemic control, proper footwear and foot care.